“Perception of Student to the Impact of Sim Card Registration Act 11934 to Cybercrime”: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Nowadays, a lot of people use gadgets not just to communicate with loved ones, but also tolessen there boredom, due to the expansion of technology and newly updated gadgets. That’swhy people get obsessed with using gadgets, which turns into bad habits; a lot of bad thingscan be learned by using the internet, especially for those children who have not been properlyguided by their parents.In line with the purpose of the study, which is to know the perception of students regarding theimpact of the SIM Card Registration Act 11934 on cybercrime, the researchers will use thedescriptive research design. The population of the study is the students at Bestlink college ofthe Philippines; specifically, the respondents comprise 50 students. The major instrumentused for gathering data was a survey questionnaire.This study gives the respondents and future researchers additional knowledge about the SIMCard Registration Act. Future researchers can focus on the respondents, such as the deliveryriders, to know their perception of the SIM Card Registration Act. Future researchers canfocus on studying the SIM Card Registration Act to gain more knowledge and understand thisnew mandatory registration act 11934. Future researchers could also focus on theadvantages and disadvantages of the newly mandatory SIM card Registration Act 11934.
Keywords: Criminology